Research prioritization of interventions for the primary prevention of preterm birth: An international survey. (May 2019) - Allotey, John; Matei, Anca; Husain, Shahid; Newton, Sian; Dodds, Julie; Armson, Anthony B.; Khan, Khalid S.; Vogel, Joshua P.
Abstract: Objective: To identify research priorities of interventions for the primary prevention of preterm birth (PTB), by conducting an international stakeholder survey. Study design: A prospective cross-sectional online survey was conducted in November 2016. Fifteen interventions to prevent spontaneous PTB were identified and ranked by stakeholders (n = 159) in the field of maternal and perinatal health research, using nine equally weighted criteria. Medians and interquartile ranges (IQRs) were calculated and the interventions ranked accordingly. Results: Respondents to the survey were from 46 different countries, mostly from low and middle-income countries (62%, 99/159) and were mainly clinicians (80%, 127/159). Of the fifteen interventions ranked, the following five were identified as research priorities in the primary prevention of PTB: dietary counselling and nutritional education, risk scoring, vitamin D supplementation, exercise and antioxidant supplementation. Conclusion: We have identified research priorities of interventions to prevent spontaneous PTB through a global stakeholder survey. The interventions prioritized in this exercise can be used by researchers, grant funding bodies and research-policy decision makers to inform calls on future clinical trials or individual patient data meta-analyses on the primary prevention of PTB.